Contrasting Two Facies of Muncung Granite in Lingga Regency Using Major, Trace, and Rare Earth Element Geochemistry - Irzon, Ronaldo (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.1.23-33Lingga Regency is located in the main range of the famous Southeast Asia granitic belt related to tin resources. There are two granitic units in this region: the S-type Muncung Granite and I-type Tanjungbuku Granite. XRF and ICP-MS were used to measure the major, trace, and rare earth elements of nine Muncung Granite samples. Two different patterns were identified from major data plotting on Harker variation diagram. Granitic rocks from Lingga and Selayar Islands are classified as A facies while others from Singkep Island is B facies. This paper used graphs and variation diagrams to reveal the differences of those two facies. Thus, REE correlation to SiO2, trace element spider diagram, and REE spider diagram show more contrasts correlation. However, both facies are syn-collisional and High-K calc-alkaline granites. Some identical characters with other granitic units in Peninsular Malaysia were also detected in this work.